Further validation of strecker-type α-aminonitriles as a new class of potent human carbonic anhydrase II inhibitors: hit expansion within the public domain using differential scanning fluorimetry leads to chemotype refinement. (1st January 2020) - Krasavin, Mikhail; Kalinin, Stanislav; Zozulya, Sergey; Griniukova, Anastasia; Borysko, Petro; Angeli, Andrea; Supuran, Claudiu T.
Abstract: Testing of an expanded, 800-compound set of analogues of the earlier described Strecker-type α-aminonitriles (selected from publicly available Enamine Ltd. Screening Collection) in thermal shift assay against bovine carbonic anhydrase ( b CA) led to further validation of this new class of inhibitors and identification a new, refined chemotype represented by inhibitors with 10-improved potency.